Target Nuclear and Off-Target Plastid Hybrid Enrichment Data Inform a Range of Evolutionary Depths in the Orchid Genus Epidendrum - Granados Mendoza, Carolina; Jost, Matthias; Hágsater, Eric; Magallón, Susana; van den Berg, Cássio; Lemmon, Emily Moriarty; Lemmon, Alan R.; Salazar, Gerardo A.; Wanke, Stefan (Frontiers in Plant Science, 2020)
Universal angiosperm enrichment probe sets designed to enrich hundreds of putatively orthologous nuclear single-copy loci are increasingly being applied to infer phylogenetic relationships of different lineages of angiosperms at a range of evolutionary depths. Studies applying such probe sets have focused on testing the universality and performance of the target nuclear loci, but they have not taken advantage of off-target data from other genome compartments generated alongside the nuclear loci. Here we do so to infer phylogenetic relationships in the orchid genus Epidendrum and closely related genera of subtribe Laeliinae. Our aims are to: 1) test the technical viability of applying the plant Anchored Hybrid Enrichment (AHE) method (Angiosperm v.1 probe kit) to our focal group, 2) mine plastid protein coding genes from off-target reads; and 3) evaluate the performance of the target nuclear and off-target plastid loci in resolving and supporting phylogenetic relationships along a range of taxonomical depths. Phylogenetic relationships were inferred from the nuclear data set through coalescent summary and site-based methods, whereas plastid loci were analyzed in a concatenated partitioned matrix under maximum likelihood. The usefulness of target and flanking non-target nuclear regions and plastid loci was assessed through the estimation of their phylogenetic informativeness. Our study successfully applied the plant AHE probe kit to Epidendrum, supporting the universality of this kit in angiosperms. Moreover, it demonstrated the feasibility of mining plastome loci from off-target reads generated with the Angiosperm v.1 probe kit to obtain additional, uniparentally inherited sequence data at no extra sequencing cost. Our analyses detected some strongly supported incongruences between nuclear and plastid data sets at shallow divergences, an indication of potential lineage sorting, hybridization or introgression events in the group. Lastly, we found that the per site phylogenetic informativeness of the ycf1 plastid gene surpasses that of all other plastid genes and several nuclear loci, making it an excellent candidate for assessing phylogenetic relationships at medium to low taxonomic levels in orchids.